Online, cross-disciplinary team science training for health and medical professionals: Evaluation of COALESCE (teamscience.net). Issue 2 (18th July 2019) - Spring, Bonnie; Klyachko, Ekaterina A.; Rak, Phillip W.; McFadden, H. Gene; Hedeker, Donald; Siddique, Juned; Bardsley, Leland R.; Pfammatter, Angela Fidler
Abstract: Introduction: The National Academies of Sciences (NAS) emphasize the need for interdisciplinary team science (TS) training, but few training resources are available. COALESCE, an open-access tool developed with National Institutes of Health support and located atteamscience.net, is considered a gold standard resource but has not previously been evaluated. COALESCE launched four learning modules in 2011. The Science of TS (SciTS) module, an interactive encyclopedia, introduces foundational concepts. Three scenario-based modules simulate TS challenges in behavioral, clinical, and basic biomedical sciences. This study examined user characteristics, usage patterns, and effects of completing the four modules on TS knowledge, attitudes, and skills. Methods: Repeated measures ANOVA tested for pre-post changes in performance and compared learning by users with biomedical versus other disciplinary backgrounds. Results: From 2011 through 2017, the site attracted 16, 280 new users who engaged in 6461 sessions that lasted more than 1 min. The modal registrant identified as working in a biomedical field (47%), in an academic institution (72%), and expressed greater interest in the practice than the SciTS (67%). Those completing pre- and post-tests ( n = 989) showed significant improvement in knowledge, attitudes, and skills after taking all scenario-based modules ( p < 0.005); knowledge and attitudes were unchanged after the SciTS encyclopedia. Biomedical and other health professionals improved comparably. Conclusion: Evaluation of the TS training tool atteamscience.net indicates broad dissemination and positive TS-related outcomes. Site upgrades implemented between 2018 and 2020, including adding five new modules, are expected to increase the robustness and accessibility of the COALESCE training resource.